The Actualization of Justice in the Settlement of Joint Assets Due to Divorce: Comparative Analysis of Decisions of the Religious Courts - Muslimin, JM.; Fatma, Yulia (Fakultas Syariah, 2020)
Abstract: The core problem examined in this paper is the practice of sharing assets in the Religious Courts. The article aims to prove that the justice provided by the judge in the distribution of joint assets is not only textually in accordance with applicable regulations, but by considering comprehensively, so that it can reflect the actuality. The urgency of this research is to emphasize that justice in the distribution of sharing assets cannot be interpreted as saying that each party must get an equal share. Justice can refer to the contributions made by both parties, both material and non-material. The used method of research focuses on a normative approach which is sharpened empirically. The normative approach requires a juridical and philosophical exploration, while empirical through the sociological approach. The results of the study conclude that the decisions of the Religious Courts regarding sharing assets are not always in accordance with the provisions of the Islamic Law Compilation (Kompilasi Hukum Islam).Keywords: justice; join assets; judges’ decision.Abstrak: Masalah utama yang dikaji dalam tulisan ini adalah praktik pembagian harta bersama di Peradilan Agama. Tulisan bertujuan untuk membuktikan bahwa keadilan yang diberikan oleh hakim dalam pembagian harta bersama tidak hanya semata tekstual sesuai aturan yang berlaku, akan tetapi dengan mempertimbangkan secara komprehensif, sehingga dapat mencerminkan sisi aktualitasnya. Urgensi penelitian ini untuk menegaskan bahwa keadilan dalam pembagian harta bersama, tidak bisa diartikan menjadi setiap pihak harus mendapatkan bagian yang sama rata. Keadilan dapat mengacu kepada kontribusi yang diberikan oleh kedua belah pihak, baik secara materi maupun non-materi. Sementara metode yang digunakan mentitikberatkan pada pendekatan normatif dan dipertajam dengan empiris. Pendekatan normatif meniscayakan uji putusan secara yuridis dan filosofis. Sedangkan empiris, melalui sisi sosiologis. Hasil penelitian menyimpulkan bahwa putusan Peradilan Agama tentang harta bersama tidak selalu sesuai dengan ketentuan Kompilasi Hukum Islam (KHI).Kata Kunci: keadilan; harta bersama; putusan hakim.